ANALISIS PENGARUH HARGA PRODUK DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (Studi Kasus Jasa bengkel Alin Motor Semarang) - Noto, Ezra Hendri; Hakim, Lukmanul (STIE AMA Salatiga, 2016)
Abstract This research is motivated complaints or customer dissatisfaction on product price and quality products provided Alin Motorcycle Workshop. These complaints should be dealt with either by the Workshop Alin Motor, because if not addressed properly, then the customer will tell the disappointing experiences to others, so it will worsen the image and the existence of the workshop. Complaints can be minimized by taking the necessary steps, so that customers will be satisfied with the price and quality and support provided by the workshop. Customer satisfaction in the long run can create customer loyalty towards Alin Motor Repair. The purpose of this study was to analyze the effect of product price and quality products which include physical evidence, reliability, product durability, to customer satisfaction Alin Motor Repair. This research was conducted by questionnaire to 100 customers Alin Motor Repair obtained by using purposive sampling technique was then performed an analysis of the data obtained in the form of quantitative analysis Quantitative analysis includes the validity and reliability test, the classical assumption test, multiple regression analysis, the test Goodness of Fit through F test and t test and the coefficient of determination (R²). The results showed that the coefficient of determination which looks at the value of Adjusted R Square of 0.224 which means that customer satisfaction can be explained by the independent variable in this study is the price of the product, and the quality of products, by 50%. While the remaining 22.4% can be explained by other variables outside of the three variables used in this study. Partially based on the results of the t test variables in this study are positive and significant effect where the price of products had the greatest influence than other variables in this study, while the quality of the product has a positive effect on customer satisfaction. F test showed that simultaneous or jointly variable in this study is the price produkdan quality products and a significant positive effect on customer satisfaction. Keywords: product price, product quality, customer satisfaction.